PENYELESAIAN KREDIT MACET DENGAN JAMINAN HAK TANGGUNGAN - Sri Retno Widyorini (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2011)
Banking is a financial institution that became one of the sources of public funds both individuals and business entities to obtain compliance with the required credits. There is a possibility that the credit extended by the creditor to the debtor cannot paid in time as it has been agreed in the credit agreement, giving rise to a problem called with bad credit. There are several factors that lead to bad credit is an internal factor of the bank itself as well as external factors that are outside the bank that could affect the occurrence of bad credit or credit problems. To overcome credit problems there are some things that can be done by the bank include the action to perform rescheduling, reconditioning or by doing a temporary capital with the conditions as set by Bank of Indonesia as the Central Bank. Loan with mortgage collateral is sort of credit which using the right to use land as guarantees according to the set in the UUPA(Undang-Undang Pokok Agraria ~ Basic Agrarian Law). Object of the land rights that is burdened by the mortgage collateral is Property Rights, Rights of Building, Rights of Business Use and Rights of Use. Besides, the object of mortgage is also regulated in Law Number 16Year 1985 about Flats.